(untitled) (REMUNOM, 2024)
: The study’s central objective is to address the role of physical exercise in the prevention of chronic diseases in the elderly, since it understands that physical exercise, in addition to training, plays a fundamental role in the prevention of chronic diseases, provides a series of benefits to physical and physical health. mental health, in addition to improving quality of life and longevity. From this context, we carried out an integrative literature review, in which complete and original studies were used, with time frames from 2014 to 2024, in Portuguese, English and Spanish. The databases PubMed, SciELO, VHL were used as a research source.